2012
DOI: 10.1007/s00467-012-2143-7
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in children with chronic kidney disease

Abstract: Background The role of vitamin D status in patients with renal insufficiency and its relation to dietary intake and parathyroid hormone (PTH) secretion is of utmost interest given the morbidity and mortality associated with the disordered mineral metabolism seen in chronic kidney disease. Methods We conducted a cross-sectional study of 100 pediatric patients with a diagnosis of CKD Stage 1–5 at Children’s Hospital Boston, measuring blood levels of 25OHD, 1,25(OH)2D, and parathyroid hormone and obtaining data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 29 publications
0
6
0
2
Order By: Relevance
“…Studies in children with CKD have reported variable associations between GFR and 25OHD deficiency [22, 24, 25]. In their study of 182 pediatric CKD patients, Kalkwarf et al showed that later stages of CKD (4, 5, and 5D) did associate with lower 25OHD concentrations [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in children with CKD have reported variable associations between GFR and 25OHD deficiency [22, 24, 25]. In their study of 182 pediatric CKD patients, Kalkwarf et al showed that later stages of CKD (4, 5, and 5D) did associate with lower 25OHD concentrations [22].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Seeherunvong et al reported that patients with more advanced CKD (stage 3 to 5 with eGFR < 60 ml/min/1.73 m 2 ) had a higher prevalence of vitamin D deficiency than those with more moderately reduced or normal eGFR (42 vs. 26 %; p <0.05) [25]. By contrast, in a study by Stein et al, in which 70 % of children had CKD stage 1 to 3, 25OHD levels did not associate with GFR [24]. We found no association between GFR and 25OHD levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption experiments were conducted to optimize the time required for maximum adsorption of phosphate onto Fe(II)-MMT. First 200 mL of aqueous solution of phosphate containing 13.1 mg of sodium dihydrogen phosphate and 6.6 mg of ascorbic acid were mixed with 100 mg of Fe(II)-MMT powder for 10,20,30,40,70,90,140,190,240, and 290 min at 37 • C in a 250-mL conical flask with constant temperature oscillation.…”
Section: Adsorption Experimentsmentioning
confidence: 99%
“…Limitation should be considered since most studies determined albumin-bound vitamin D, although unbound (bioavailable) may be a superior marker [53]. Stein et al [54] found a deficiency in 16 and 24% of patients and a significant correlation of 25OH D, but not calcitriol, to PTH. Looking at all stages of pediatric CKD, vitamin D deficiency was found in 42.6%, and 34.4% showed vitamin D insufficiency [17].…”
Section: Diagnostic Approachmentioning
confidence: 99%